Evaluation of the “Multivariable Psoriatic Arthritis Risk Estimation Tool” in a Cohort of Patients with Psoriasis: Preliminary Results of a Prospective Observational Study - Ennio Lubrano; Filomena Mandato; Marcella Antenucci; Fabio Massimo Perrotta (Rheumatology and Therapy)
Abstract Introduction An intriguing aspect that emerged in recent years is the transition phase from psoriasis (PsO) to psoriatic arthritis (PsA). The PRESTO instrument allows estimating a patient’s risk of developing PsA based on a few clinical items. The aim of this study was to apply and evaluate the performance of the PRESTO tool in a cohort of patients with PsO. Methods Consecutive patients with PsO were enrolled. Dermatological and rheumatological assessment was carried out in order to evaluate clinical features of PsO, to exclude the diagnosis of PsA, and to administer the PRESTO tool. Results Between January 1, 2024 and April 1, 2024, 100 patients were assessed. Eight-four patients found the questionnaire to be very useful and easy. The estimated risk (median/IQR) of 1-year progression to PsA found in our group was 2.45% at 1 year (1.1–4). Conclusions The PRESTO instrument was feasible and well accepted by patients. The 1-year risk assessed by PRESTO tools is consistent with other reports in the literature.